Management of Trastuzumab Deruxtecan-related nausea and vomiting in real-world practice - Notini, Giulia; Naldini, Matteo Maria; Sica, Lorenzo; Viale, Giulia; Rognone, Alessia; Zambelli, Stefania; Zucchinelli, Patrizia; Piras, Marta; Bosi, Carlo; Mariani, Marco; Aldrighetti, Daniela; Bianchini, Giampaolo; et al. (Frontiers in Oncology, 2024)
Background Nausea and vomiting are common side effects of Trastuzumab Deruxtecan (T-DXd), but guidelines for optimal management were not initially available. This retrospective single-center study aimed at evaluating the efficacy of two antiemetic regimens in patients receiving T-DXd. Methods Data from metastatic breast cancer patients receiving T-DXd were collected. Two groups were defined: patients treated with 5-HT3 receptor antagonists (RA) ± dexamethasone (5-HT3-group) and patients treated with a fixed oral combination of netupitant (NK1RA) and palonosetron ± dexamethasone (NK1 group). Physicians preferentially offered the NK1 regimen to patients at higher risk of nausea and vomiting based on internal recommendations. Only nausea and vomiting during cycles 1 and 2 were considered. Comparisons of nausea and vomiting by the antiemetic prophylaxis group were assessed using chi-square. Results A total of 53 patients were included in the analysis. At cycle 1, 72% and 28% of patients received the 5-HT3 and NK1 prophylaxis, respectively. Overall, 58% reported nausea, with no differences between groups (58% vs. 60%; p = 0.832), but with a trend for lower grade in the NK1 group (33.3% G1; 26.7% G2) compared to the 5-HT3 group (23.7% G1; 31.6% G2; 2.6% G3). Vomiting was reported by 21% and 0% of patients in the 5-HT3 and the NK1 group, respectively (p = 0.054). Among the 15 patients in the 5-HT3 group with nausea at cycle 1 who escalated to NK1 at cycle 2, nausea decreased from 100% to 53% (p = 0.022) and vomiting decreased from 47% to 13% (p = 0.046). Conclusions The NK1 regimen improved vomiting control at cycle 1 and, when introduced at cycle 2, significantly improved both nausea and vomiting. The biased NK1 selection for higher-risk patients may have dampened the differences between groups at cycle 1. These findings support enhanced control of T-DXd-related nausea and vomiting with NK1RA.